The integrin αvβ6 drives pancreatic cancer through diverse mechanisms and represents an effective target for therapy. Issue 3 (30th July 2019) - Reader, Claire S; Vallath, Sabari; Steele, Colin W; Haider, Syed; Brentnall, Adam; Desai, Ami; Moore, Kate M; Jamieson, Nigel B; Chang, David; Bailey, Peter; Scarpa, Aldo; Lawlor, Rita; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a 5‐year survival rate of less than 4% and desperately needs novel effective therapeutics. Integrin αvβ6 has been linked with poor prognosis in cancer but its potential as a target in PDAC remains unclear. We report that transcriptional expression analysis revealed that high levels of β6 mRNA correlated strongly with significantly poorer survival ( n  = 491 cases, p  = 3.17 × 10 −8 ). In two separate cohorts, we showed that over 80% of PDACs expressed αvβ6 protein and that paired metastases retained αvβ6 expression. In vitro, integrin αvβ6 promoted PDAC cell growth, survival, migration, and invasion. Treatment of both αvβ6‐positive human PDAC xenografts and transgenic mice bearing αvβ6‐positive PDAC with the αvβ6 blocking antibody 264RAD, combined with gemcitabine, significantly reduced tumour growth ( p  < 0.0001) and increased survival (log‐rank test, p  < 0.05). Antibody therapy was associated with suppression of tumour cell activity (suppression of pErk growth signals, increased apoptosis seen as activated caspase‐3) and suppression of the pro‐tumourigenic microenvironment (suppression of TGFβ signalling, fewer αSMA‐positive myofibroblasts, decreased blood vessel density). These data show that αvβ6 promotes PDAC growth through both tumour cell and tumour microenvironment mechanisms and represents a valuable target for PDAC therapy. © 2019 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.